Liquid-Liver Phantom: Mimicking the Viscoelastic Dispersion of Human Liver for Ultrasound- and MRI-Based Elastography - Morr, Anna S.; Herthum, Helge; Schrank, Felix; Goerner, Steffen; Anders, Matthias S.; Lerchbaumer, Markus; Mueller, Hans-Peter; Fischer, Thomas; Jenderka, Klaus-Vitold; Hansen, Hendrik H. G.; Janmey, Paul A.; Braun, Juergen; et al. (Investigative Radiology, 2022)
Objectives Tissue stiffness can guide medical diagnoses and is exploited as an imaging contrast in elastography. However, different elastography devices show different liver stiffness values in the same subject, hindering comparison of values and establishment of system-independent thresholds for disease detection. There is a need for standardized phantoms that specifically address the viscosity-related dispersion of stiffness over frequency. To improve standardization of clinical elastography across devices and platforms including ultrasound and magnetic resonance imaging (MRI), a comprehensively characterized phantom is introduced that mimics the dispersion of stiffness of the human liver and can be generated reproducibly. Materials and Methods The phantom was made of linear polymerized polyacrylamide (PAAm) calibrated to the viscoelastic properties of healthy human liver in vivo as reported in the literature. Stiffness dispersion was analyzed using the 2-parameter springpot model fitted to the dispersion of shear wave speed of PAAm, which was measured by shear rheometry, ultrasound-based time-harmonic elastography, clinical magnetic resonance elastography (MRE), and tabletop MRE in the frequency range of 5 to 3000 Hz. Imaging parameters for ultrasound and MRI, reproducibility, aging behavior, and temperature dependency were assessed. In addition, the frequency bandwidth of shear wave speed of clinical elastography methods (Aplio i900, Canon; Acuson Sequoia, Siemens; FibroScan, EchoSense) was characterized. Results Within the entire frequency range analyzed in this study, the PAAm phantom reproduced well the stiffness dispersion of human liver in vivo despite its fluid properties under static loading (springpot stiffness parameter, 2.14 [95% confidence interval, 2.08-2.19] kPa; springpot powerlaw exponent, 0.367 [95% confidence interval, 0.362-0.373]). Imaging parameters were close to those of liver in vivo with only slight variability in stiffness values of 0.5% (0.4%, 0.6%), 4.1% (3.9%, 4.5%), and -0.63% (-0.67%, -0.58%), respectively, between batches, over a 6-month period, and per °C increase in temperature. Conclusions The liquid-liver phantom has useful properties for standardization and development of liver elastography. First, it can be used across clinical and experimental elastography devices in ultrasound and MRI. Second, being a liquid, it can easily be adapted in size and shape to specific technical requirements, and by adding inclusions and scatterers. Finally, because the phantom is based on noncrosslinked linear PAAm constituents, it is easy to produce, indicating potential widespread use among researchers and vendors to standardize liver stiffness measurements.
CRIS-Team Scopus Importer:2022-08-03
Keywords: elastography; liver; magnetic resonance elastography; phantom; shear modulus; shear viscosity; shear wave dispersion; ultrasound elastography; viscoelasticity